2021
DOI: 10.1002/jcsm.12856
|View full text |Cite
|
Sign up to set email alerts
|

Increased odds of having the metabolic syndrome with greater fat‐free mass: counterintuitive results from the National Health and Nutrition Examination Survey database

Abstract: Background It is well established that body composition influences metabolic health, but emerging data are conflicting with the largely purported idea that a large fat‐free mass (FFM) has a protective effect on health. A potential explanation for these discrepancies is the way FFM is represented. The first objective is to determine the association between the metabolic syndrome (MetS) and FFM when the latter was represented in three different ways: 1—absolute FFM; 2—relative to squared height (FFMi); and 3—rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
4
5
0
Order By: Relevance
“…On the contrary, high ALM/height 2 or high absolute ALM had significantly higher incident of MetS during the follow-up period. This is consistent with the recent crosssectional study [24] and previous studies [7][8][9][10][11][12][13][14]. It is because the people who have higher body weight tend have higher muscle mass.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, high ALM/height 2 or high absolute ALM had significantly higher incident of MetS during the follow-up period. This is consistent with the recent crosssectional study [24] and previous studies [7][8][9][10][11][12][13][14]. It is because the people who have higher body weight tend have higher muscle mass.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study are consistent with these reports, and this is the first prospective study to examine the association between low ALM/Wt and MetS development, to the best of our knowledge. In contrast, high ALM/Ht 2 showed significantly higher MetS incidence during the follow-up period, which is consistent with a recent cross-sectional study [ 36 ] and previous studies [ 10 17 ]. However, most of the previous studies did not take into account the effect of fat mass or percent body fat on the association between ALM and MetS development.…”
Section: Discussionsupporting
confidence: 92%
“…However, people with a higher body weight exhibit higher muscle mass and strength, and previous studies indicated that the normalization of muscle mass or strength by body weight or body mass index (BMI) is needed to see the association between SMM or strength and MetS [ 10 17 ]. Previous cross-sectional studies indicated that relative ALM per kg weight (ALM/Wt) or BMI (ALM/BMI) are inversely associated with MetS [ 10 17 ], but relative ALM (or fat-free mass) per squared height (ALM/Ht 2 ) or absolute ALM (or fat-free mass) are positively associated with MetS [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it is a common misconception that increased weight status is predominately attributable to FM accumulation. To the contrary, within the framework of the obesity epidemic, absolute FFM and FM typically increase in tandem resulting in cardiometabolic abnormalities regardless of total FFM (48), evident by studies reporting an increased risk of MetS with greater FFM (49). As such, it is important to consider these associations in the appropriate context given that they may be distorted by whole body hypertrophy, particularly for young adults.…”
Section: Discussionmentioning
confidence: 99%